Willingness to Pay for Quality Seeds: Field Experimental and Survey Data, Tanzania Bean Study, 2015-16 - Mywish K., Maredia; Shupp, Robert; Mishili, Fulgence; Reyes, Byron A.; Kusolwa, Paul; Kudra, Abdul (International Center for Tropical Agriculture, 2019)
This dataset includes results of double blind field experiments and experimental auctions conducted with bean farmers in Tanzania to gauge the relative demand for four types of seed products--i.e., certified 1, certified 2, quality declared, and recycled seed. Files include data on: a) farmer rating of the four seed quality types planted in the farmer managed field demonstration plots; b) farmer’s bid on these four seed quality types during the seed auction experiments conducted on the second field day before harvest; c) farmer survey data; and d) field experiment yield data. (2019-04-27).